PEMBUATAN DAN KARAKTERISASI MEMBRAN ELEKTRODA SELEKTIF ION CD(II) BERBASIS PVC DENGAN NA2S SEBAGAI IONOFOR - Zahra Ourelya Nazzala; Aman Sentosa Panggabean; Noor Hindryawati (PROSIDING SEMINAR KIMIA, 2025)
Preparation and characterization of Cd2+ ion selective electrode membrane using sodium sulfide (Na2S) as an ionophore has been conducted. This research aims to create and characterize Cd2+ ion selective electrode membrane as a chemical sensors. Membrane of ion selective electrode was made with the optimum composition with ratio of Na2S : PVC : DOP was 6 : 3 : 1. The membrane was doped using 1 M Cd2+ solution for 7 days, and characterized using FT-IR spectroscopy. FT-IR characterization used to determine the shift of wave number from absorption spectrum, the results showed the absorption 851 cm-1 wave lenght is Cd–S bond. ion selective electrode Cd2+-Na2S characterization show that ion selective electrode worked well with an internal solution composition 1:3 with the linear concentration range 1×10-4 - 1×10-1 M, with Nernst factor was 29.87 mV/decade and the limit of detection was 5.71×10-5 M as a Cd(CH3COO)2 concentration or equivalent to Cd2+ concentration of 0.6422 ppm. Ion selective electrode worked optimally in the pH range 4-6, with the response time was 10-60 seconds and can be used up to 5 days. The presence of interfere ions such as Cu2+, Zn2+, Cl-, NO3-, and SO42- didn’t affect the performance of ion selective electrode Cd2+-Na2S determining Cd2+ ions in the samples. Keywords: Cd(II), Ion selective Electrodes, PVC membrane, Na2S.